A comparative study of the Z-N, adaptation law and PSO methods of tuning the PID controller of a synchronous machine - Kasilingam G.; Pasupuleti J. (Praise Worthy Prize S.r.l, 2023)
A proportional–integral–derivative (PID)-based power system stabilizer (PSS) was designed to damp low-frequency oscillations in power systems under different operating conditions. The parameters of the PID controller were tuned using a particle swarm optimization (PSO) algorithm. The performance of the PSO-PID-type PSS was thoroughly investigated and compared with those of the Ziegler–Nichols (Z-N) and adaptation law methods. The effectiveness of the PSO-PID with PSS is applied to a single-machine infinite-bus system connected to a nonlinear load with different kinds of faults. The variations in the speed deviation, rotor angle and load angle were compared in a Simulink based MATLAB environment. The damping performance of the PSO-PID controller over a wide range of operating conditions is excellent. © 2014 Praise Worthy Prize S.r.l. - All rights reserved.